The Legal Protection for Victims of Domestic Violence in Indonesia - Widodo, Hendro (Universitas Islam Sultan Agung, 2025)
Domestic violence (DV) is a serious social problem and requires special attention from the legal aspect in order to protect victims comprehensively. This journal discusses legal protection for victims of domestic violence with a focus on three main aspects, namely victims' rights, reporting mechanisms and temporary protection, and efforts to restore and assist victims. First, the rights of victims of domestic violence are guaranteed by Law Number 23 of 2004 concerning the Elimination of Domestic Violence, which includes the right to physical and psychological protection, health services, legal assistance, and guarantees of the confidentiality of the victim's identity. These rights aim to provide a sense of security and support the victim's recovery process comprehensively. Second, the reporting mechanism and temporary protection are crucial initial steps in handling cases of domestic violence. Victims or their attorneys can report violence to the police, who are required to provide temporary protection within 1x24 hours after the report is received, valid for seven days while waiting for the determination of protection from the court. This protection includes physical and psychological security so that victims are protected from threats from the perpetrator during the legal process. Third, efforts to restore and assist victims are an important part of the rehabilitation process for victims of domestic violence. Assistance includes psychological counseling, legal advocacy, and spiritual guidance carried out by professional staff and related institutions in an integrated manner. This approach aims to restore the physical and mental condition of the victim and ensure that their rights are optimally restored. This journal concludes that legal protection for victims of domestic violence must be comprehensive, covering aspects of protection, law enforcement, and recovery so that victims can obtain justice and a decent life after experiencing violence. Effective implementation requires synergy between law enforcement officers, social institutions, and the community.